2019
DOI: 10.1016/j.etap.2018.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Acute exposure to a glyphosate-containing herbicide formulation inhibits Complex II and increases hydrogen peroxide in the model organism Caenorhabditis elegans

Abstract: Glyphosate-based herbicides, such as Touchdown (TD) and Roundup, are among the most heavilyused herbicides in the world. While the active ingredient is generally considered non-toxic, the toxicity resulting from exposure to commercially-sold formulations is less clear. In many cases, cell cultures or various model organisms exposed to glyphosate formulations show toxicity and, in some cases, lethality. Using Caenorhabditis elegans, we assessed potential toxic mechanisms through which a highly-concentrated comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…The detrimental impact of GBHs on mitochondrial activity has already been demonstrated in Caenorhabditis elegans, as exposing these animals to 3% TouchDown (expressed as % glyphosate; TouchDown Hitech, formulation of 52.3% glyphosate) leads to a decrease in mitochondrial respiration, oxygen consumption and ATP production, and an increase in intracellular levels of hydrogen peroxide 40 . These toxic effects have been suggested to be exerted through the impairment of the electron transport chain function via inhibition of Complex II (succinate dehydrogenase) 40,41 . Moreover, Roundup has been demonstrated to reduce the activity of mitochondrial succinate dehydrogenase in an immature mouse Sertoli TM4 cell line at a concentration as low as 0.001%, with heavier toxic effect than glyphosate alone 42 .…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental impact of GBHs on mitochondrial activity has already been demonstrated in Caenorhabditis elegans, as exposing these animals to 3% TouchDown (expressed as % glyphosate; TouchDown Hitech, formulation of 52.3% glyphosate) leads to a decrease in mitochondrial respiration, oxygen consumption and ATP production, and an increase in intracellular levels of hydrogen peroxide 40 . These toxic effects have been suggested to be exerted through the impairment of the electron transport chain function via inhibition of Complex II (succinate dehydrogenase) 40,41 . Moreover, Roundup has been demonstrated to reduce the activity of mitochondrial succinate dehydrogenase in an immature mouse Sertoli TM4 cell line at a concentration as low as 0.001%, with heavier toxic effect than glyphosate alone 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Given their implication in oxidative stress, GBHs are inclined to alter energy metabolism and cellular biochemical processes as well. Indeed, in C. elegans exposed to environmentally-relevant concentrations of Touchdown V R , a reduction in oxygen consumption and complex II activity was noted, suggesting a decrease in mitochondrial respiration; but complex IV seems unscathed, with its activity even increased (Burchfield et al 2019). This observation could indicate that GBHs affect mitochondrial respiration upstream of complex IV.…”
Section: Cellular Effectsmentioning
confidence: 99%
“…In Caenorhabditis elegans, increased hydrogen peroxide (H 2 O 2 ) production was observed after Touchdown V R exposure (Burchfield et al 2019). Environmentally-realistic concentrations of GBHs also lower the activity of anti-oxidant enzymes, i.e.…”
Section: Cellular Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most studied aspect of glyphosate toxicology is its oxidative stress inducing properties. Glyphosate is known to affect mitochondria in mammalian cells, generating oxidative stress (Burchfield et al 2019;El-Shenawy 2009). Caecal metabolomics in our study showed that glyphosate affected gamma-glutamyl amino acid metabolism in the microbiome (Figure 2).…”
Section: Discussionmentioning
confidence: 60%